Integrating pelagic and coastal MPAs into large‐scale ecosystem‐wide management. Issue 1 (6th December 2012) - Guidetti, P.; Notarbartolo‐Di‐Sciara, G.; Agardy, T.
ABSTRACT Marine Protected Areas (MPAs) have gained increasing popularity worldwide as tools for biodiversity conservation and management of human uses. This rise in popularity has been accompanied by an increasing body of scientific papers and books on MPA design and management, the vast majority of which are almost completely focused on coastal or insular MPAs. A small number of MPAs have also been established in the pelagic domain, however, these pelagic sites have been considered in isolation from coastal/insular MPAs, even when the sites are adjacent or nearby. Pelagic and coastal ecosystems are not at all isolated from each other, but interconnected both physically via the flow of water, and biologically, via the movement of organisms. In order to maximize the effectiveness of MPAs, it is suggested that spatial management planning encompass large areas that span both coastal and pelagic domains. This requires integrated, large‐scale spatial management, which may extend across borders and thus require international cooperation. Copyright © 2012 John Wiley & Sons, Ltd.